Red Ribbon Skirts and Cultural Resurgence: Kimihko sîmpân iskwêwisâkaya êkwa sihcikêwin waniskâpicikêwin. Issue 3 (1st December 2019) - Wuttunee, Kari Dawn; Altenberg, Jennifer; Flicker, Sarah
Abstract : A small group of Indigenous girls and their allies came together to make ribbon skirts to reclaim teachings, resist gender-based and colonial violence, and re-imagine our collective futures. Based on the personal reflections of the organizers and the girls involved gathered through individual semi-structured interviews and directed journal writing, we share lessons about the process and outcomes. Learning about the historical and cultural significance of ribbon skirts gave these girls a stronger connection to their culture, community, and each other. Wearing their ribbon skirts became an embodied act of resistance to violence in promoting resilience and self-determination. This case study illustrates how Indigenous girls and their allies can engage in resurgence practices to challenge gender-based violence through reclaiming and adapting cultural teachings and practices.